2021
DOI: 10.3892/mmr.2021.12435
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomal‑miR‑1184 derived from mesenchymal stem cells alleviates cisplatin‑associated acute kidney injury

Abstract: Acute kidney injury (AKI) poses a severe threat to human health. MicroRNAs (miRNAs/miRs) are known to be involved in the progression of AKI; however, the function of miR-1184 in AKI remains unclear. Thus, the aim of the present study was to examine the role of this miRNA in kidney injury. In order to mimic AKI in vitro , HK-2 cells were treated with cisplatin. Bioinformatics analysis was performed to explore the differentially expressed miRNAs in AKI. A Cell Counting Kit-8 assay and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…miRNAs are a class of endogenous noncoding single-stranded RNA molecules with a length of approximately 22 nucleotides that are widely found in eukaryotes, and they perform important roles in organism development, cell differentiation and homeostasis [ 31 33 ]. Recent studies have demonstrated that MSC-Exos exert protective effects through miRNAs in multiple kidney diseases [ 34 36 ]. Therefore, we speculated that certain miRNAs contained in exosomes may be involved in the alleviation of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a class of endogenous noncoding single-stranded RNA molecules with a length of approximately 22 nucleotides that are widely found in eukaryotes, and they perform important roles in organism development, cell differentiation and homeostasis [ 31 33 ]. Recent studies have demonstrated that MSC-Exos exert protective effects through miRNAs in multiple kidney diseases [ 34 36 ]. Therefore, we speculated that certain miRNAs contained in exosomes may be involved in the alleviation of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of this, Cao et al (2021) confirmed that sEV-miR-125b-5p from mesenchymal stem cells (MSCs) could stimulate tubular repair by suppressing p53 in AKI. Similarly, our laboratory discovered that sEV-miR-1184 from MSCs can mitigate cisplatin-associated AKI ( Zhang et al, 2021 ). Additionally, sEVs from three-dimensional (3D) cultures of human placental MSCs (hPMSCs) have been reported to be effective for the treatment of AKI ( Zhang et al, 2022 ).…”
Section: Roles Of Sev-ncrnas In Akimentioning
confidence: 96%
“…[60] Additionally, recent reports have demonstrated that hypoxic mesenchymal stem cells ameliorate acute kidney ischemiareperfusion injury via enhancing renal tubular autophagy, [65] and exosomal-miR-1184 derived from MSCs alleviates cisplatin-associated AKI in in vitro model using renal HK2 cells. [66]…”
Section: Mirnasmentioning
confidence: 99%